Procampylaspis sordida Hale 1945 - Petrescu, Iorgu (Zenodo, 2006)
Procampylaspis sordida Hale, 1945 Procampylaspis sordida Hale, 1945: 215, fig. 49. Material examined . 1 female (stn SLOPE 27), NMV J53011; 3 females (stn SLOPE 45), NMV J53012; 7 females, 1 male (stn SLOPE 46), NMV J53013; 2 females (stn SLOPE 46), MGAB CUM 1620. Distribution . Off Eden, NSW and Tas.; 60–800 m depth. Remarks . Hale recorded the species from New South Wales. New records are from Tasmania at 800 m depth. Published as part of Petrescu, Iorgu, 2006, Nannastacidae (Crustacea: Cumacea) from eastern Bass Strait, the south-eastern Australian slope, and Antarctica in the collections of Museum Victoria, pp. 129-173 in Memoirs of Museum Victoria 63 (2) on page 159, DOI:10.24199/j.mmv.2006.63.14, http://zenodo.org/record/10665606